2016
DOI: 10.1111/cea.12703
|View full text |Cite
|
Sign up to set email alerts
|

Immediate hypersensitivity to iodinated contrast media: diagnostic accuracy of skin tests and intravenous provocation test with low dose

Abstract: For immediate hypersensitivity reaction to ICM, the NPV for skin tests and IPT with low dose was 80% (95% CI 44-97%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
4
21
0
1
Order By: Relevance
“…A study looked at the effect of a low dose (10 mL) ‘intravenous provocation test’ in 36 patients with a definite history of HR from ICM 17. Only one of the 36 patients who were administered 10 mL of ICM had a reaction,note that 15 patients were challenged with the culprit ICM 17. Other studies used larger volumes of up to 120 mL of ICM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study looked at the effect of a low dose (10 mL) ‘intravenous provocation test’ in 36 patients with a definite history of HR from ICM 17. Only one of the 36 patients who were administered 10 mL of ICM had a reaction,note that 15 patients were challenged with the culprit ICM 17. Other studies used larger volumes of up to 120 mL of ICM.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with a history of mild HR who were not premedicated and had no reaction, a 1-hour monitoring period may be adequate since most allergy clinics observe their patients for an hour after skin testing. Two hours is ideal in patients with a history of moderate HRs but had no reaction to the ICM, based on the occurrence of HR 2 hours after the intravenous provocation test of Sese et al 17. Patients with history of late HRs need to be cautioned about this possibility and should be contacted within a week after exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review of allergy testing following apparent immediate‐type reactions to iodinated contrast media, Sese et al found a reasonable negative predictive value from skin prick and intradermal testing; however, they did identify patients who appeared to pass an intravenous challenge test, but later reaction to contrast media again . This supports international recommendations to consider repeat allergy testing in patients with a high likelihood of drug allergy (at least for beta‐lactam allergy), including drug provocation testing, even if they pass the initial challenge test .…”
Section: Clinical Allergymentioning
confidence: 90%
“…Intravenous drug provocation test (DPT) with a skin testenegative contrast agent (ICM or GBCM) has been increasingly described, but it is neither part of routine allergological workup yet nor standardized and validated. 39,59,[61][62][63][64] For fluorescein, conjunctival DPT has been reported as additional diagnostical step when all skin tests were negative. 65 Severe reactions to DPT have been reported, and DPT could cause side effects such as kidney damage when using ICM or nephrogenic systemic fibromatosis when using GBCM.…”
Section: Drug Provocation Testmentioning
confidence: 99%